FINDINGS ON THE COORDINATION SCHOOL CHILDREN - Grosu Bogdan-Marius (Editura Univeristatii "Stefan cel Mare" din Suceava, 2018)
The importance of physical education of children of school age is conditional upon preparation of a healthy generation, physically developed, a citizen apt to perform fully the functions of the contemporary society. From the moment of birth, the child's movement becomes not only a means of physical development, but also an accumulation of information, knowledge and self-awareness of the surrounding world . Thus, as an important factor in shaping the child needs to consider creating cognitive- motor activity, which can contribute to the gradual and timely experience driving, especially during the initial awareness (6-8 years). The object of research is the process of psychomotor education at the age of 8-10 years in the pupil educational system small, reflected in a study on ascertaining coordinative abilities